THE IMPLEMENTATION OF STUDENTS FACILITATOR AND EXPLAINING MODEL THROUGH VIDEO BLOG (VLOG) TO ENHANCE SPEAKING SKILL - Nursamsilis Lutfin; Andi Hamzah Fansury (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2020)
Student Facilitator and Explaining Learning Model is a learning model where students learn to present ideas / opinions to other fellow students. This learning model is effective for training students to speak to convey their own ideas or opinions. This learning model will be relevant if students actively participate in designing the learning material to be presented. By collaborating students' ideas into video blogs or digital content that can be uploaded on social media such as Instagram, YouTube or Facebook, it is hoped that students can improve their speaking skills and be able to motivate students in the language learning process. This study used a quasi-experimental method. The population of this study is the ninth grade of SMPN 35 Makassar in the academic year 2020/2021. This study uses cluster random sampling. The sample in the study consisted of 60 students who were in two groups; 30 students in the control group and 30 students in the experimental group. The research data were collected using speaking tests, which was analyzed descriptively, and inferential statistics through the SPSS version 22 program for Windows. The results of this study indicate that there was a significant improvement after the implementation of the Student Facilitator and Explaining Learning Model on students' speaking skills. Based on these results, it is hoped that teachers, principals and stakeholders with an interest in education development can apply this learning model in terms of improving students' speaking skills and increasing student motivation in learning languages.